Penyuluhan Peningkatan Antusiasme Remaja Mengikuti Posyandu Remaja di Desa Cipinang - Julaekha, Siti; Megawati, Irma; Siswanto, Siswanto (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This research was conducted based on facts in the field, the lack of enthusiasm among teenagers to attend youth posyandu has a big impact on the quality of teenagers in the village. The absence of control and assistance for teenagers means that the quality of teenagers also declines. Collaborating with village health components and also giving appreciation to healthy teenagers so that it becomes an attraction for them to always attend youth posyandu activities. Using the Participatory Action Research (PAR) method, we look for problems in the field and then follow up on these problems. It is very clear that the youth posyandu has an important position in controlling the growth of teenagers in Cipinang Village.